Asymmetric Communication and Internal Exclusion in Everyday Political Talk - Schmitt-Beck, Rüdiger (Frontiers in Political Science, 2022)
Citizens' everyday political talk is the foundation and mainspring of deliberative democracy. Accordingly, citizens' equal and inclusive participation in political discussions is deemed crucial for this “talk-centric” vision of normatively superior democratic will-formation. Yet, discussing politics is a quite demanding activity, and research has shown that de facto not everyone has equal access to this arena of political communication. Some citizens talk about public affairs almost constantly, others more sparingly, and yet others not at all. These inequalities reflect imbalances in structural and psychological resources. Little is known, however, about what happens once individuals have entered conversations about public affairs. The article breaks new ground by examining communicative asymmetries that ordinary people experience when talking about politics with members of their overall and core networks. By muting their voices they disadvantage certain citizens, thus impairing the discursive equality that is essential for deliberative democracy. Drawing on a unique high-quality survey conducted in Germany, the article finds such experiences to take different forms of which some are quite widespread. Many citizens resort to passive listening and contribute little to unfolding conversations. Smaller shares misrepresent their true standpoints, change subjects to avoid problematic topics, drop out of unpleasant conversations, or feel silenced by other interlocutors. The article contextualizes these communicative asymmetries in the broader theoretical framework of deliberative democrats' conception of discursive inequality. To examine how they come about it proposes and tests a model of internal exclusion that refers to social structural inequality, psychological dispositions, and attributes of the discussant networks within which political conversations take place. Social structural inequality is found to be of limited relevance. Individuals' communicative efficacy and orientations toward political conflict are more important predictors of their ability to cope with the challenges of political talk than aspects of general politicization like political interest, attitude strength and internal efficacy. Encountering political disagreement is normatively central for deliberative democracy, but empirically it stands out as a powerful social driver of asymmetric communication. Its impact is strongly conditioned by individuals' structural attributes and psychological dispositions.